The Role of Artificial Intelligence (AI) in Early Childhood Education Learning Evaluation - Wilhelmus Labobar; Hendra Helwaun; Frangklin. S. Dahoklory; Sendry R. Dahoklory (Soshum: Jurnal Sosial dan Humaniora, 2026)
This qualitative study examines the role of Artificial Intelligence (AI) in early childhood education learning evaluation. Data were obtained through a review of recent literature and interviews with 10 purposively selected teachers, lecturers, and educational technology practitioners. The findings indicate that AI can support adaptive and personalised assessment, provide timely feedback, integrate data across learning environments, and facilitate the early identification of children’s needs. However, its implementation is constrained by limited teacher digital competency, unequal technological infrastructure, and concerns about children’s data privacy. AI should therefore complement, rather than replace, teachers and be introduced gradually through educator training, infrastructure development, appropriate policies, and robust data protection.